The integron prevalence of extended-spectrum beta-lactamase producing enterobacterial isolates in a Malaysian teaching hospital - Ibrahim, N.; Wajidi, M.F.; Yusof, M.Y.; Tay, S.T. (2012)
The increased frequency of antibiotic resistance is known to be associated with the dissemination of integrons in the Enterobacteriaceae. This study determined the prevalence and type of integrons amongst 160 extended-spectrum beta-lactamase producing enterobacterial isolates kept in our culture collection. Integrons were detected in 98(61.3%) isolates, including 28(62.2%) Escherichia coli, 34(64.2%) Klebsiella spp., 27(61.4%), Enterobacter spp. and 9(50.0%) Citrobacter spp. investigated in this study. Restriction analysis of the integron gene fragments revealed that class I integron was the principal integron detected in 92(57.5%) of our isolates. Class II integron was detected in 6(3.8%) of our isolates, while no class III integron was detected in this study. The high rates of integron prevalence particularly of the class I integron in the E. coli and Klebsiella spp. concur with previous studies in other geographical regions. The higher (≥50%) integron prevalence of Citrobacter and Enterobacter isolates comparing to previous studies suggests the potential of these isolates as sources for dissemination of resistance determinants. The finding in this study serves as a basis for further study on the antibiotic resistance mechanisms of enterobacterial species in this teaching hospital.